Assessing the effects of luminescently labelled and non-labelled PET nanoparticles on environmental bacteria - Krysiak-Smułek, Klaudia; Smułek, Wojciech; Przybylska, Dominika; Hnatejko, Zbigniew; Kaczorek, Ewa; Grzyb, Tomasz (Elsevier, 2025)
Manufacturers use polyethylene terephthalate (PET) to create many everyday objects, which break down into nanoparticles when released into the environment. This fact raises questions about the effects of nanometric PET on living organisms, including bacteria. However, studies on nanoPET are rare and challenging, even if only because its detection and visualisation are difficult. We studied nanoPET toxicity on selected bacteria and tested its visualisation in biological samples using three nanoPET types: pure, labelled with upconverting nanoparticles (UCNPs), and labelled with Eu3+ complex compound. The resulting colloids were characterized using dynamic light scattering, zeta potential, and emission measurements. The results confirmed the development of a method for preparing a stable aqueous colloid of nanoPET. Toxicity tests on Bacillus, Lelliottia, and Pseudomonas strains were carried out using the AlamarBlue method, along with measurements of Glutathione S-Transferase enzyme activity. The impact of labelled and non-labelled nanoPET on bacterial carbon utilisation of different sources was also evaluated. Crystal violet and the o-nitrophenyl-β-D-galactoside assays were applied to assess changes in membrane permeability. The adhesion of nanoPET to bacterial cells was examined using atomic force microscopy, and biofilm alterations were visualised under an optical microscope. UCNPs enabled the detection of nanoPET aggregation in bacterial biofilms. PET nanoparticles had a neutral or stimulating effect on bacterial growth. Cell membrane permeability varied depending on the bacterial strain and the type of nanoPET used. The results offer valuable insight into the environmental impact of nanoPET and demonstrate the effectiveness of the new nanoplastic labelling and detection method.